COMMON CHALLENGES STUDENTS ENCOUNTER IN DEVELOPING EFFECTIVE ENGLISH SPEAKING SKILLS (Universal International Scientific Journal, 2026)
This article analyzes the difficulties that students encounter in developing their English speaking skills in different educational and social settings. The article mainly highlights the fact that psychological barriers such as anxiety, insecurity, and a lack of self-confidence significantly limit students' speaking activities. The study discusses how the lack of sufficient practical training and limited opportunities to encounter English in real life negatively affect students' communication skills. It also discusses the impact of teaching methods, the classroom environment, and pedagogical approaches on the development of speaking skills. The article concludes with practical recommendations aimed at helping students overcome these barriers and increase their ability to speak English fluently.
Keywords: English speaking skills; language learning; communication